Non-restorative cavity control on proximal carious lesion of primary maxillary incisors - ์Niwat Thanaboonyang; Busayarat Santiwong; Pornpun Asvanit (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE: Early childhood caries (ECC) is a high-prevalence infectious disease with significant unmet dental care needs globally. This study aimed to compare the clinical success rates of nonrestorative cavity control (NRCC) using disking with a restorative approach (RA) using a resin-modified glass ionomer (RMGI) restoration on the proximal surfaces of the primary maxillary incisors with dental caries.METHODOLOGY: 108 proximal caries in 42 children aged 3–5 years met the inclusion criteria; caries were limited to the outer-to-middle-third of the dentin with no pulpal or periapical pathology.  The study included two experimental groups: the NRCC group was treated with proximal disking and applying 5% sodium fluoride varnish, while the RA group received RMGI Class III restorations. The follow-up period was 20 months. The 20-month cumulative survival rates were estimated using the Kaplan-Meier survival analysis, and the differences between the groups were analyzed using the Log-rank test.RESULTS: The cumulative survival probability for the NRCC group was 71.4%, while the RA group demonstrated a 71.7% success rate after 20 months. The survival probabilities between the two caries management modalities were similar (p = 0.963).CONCLUSION: The clinical success rates of NRCC using disking or RA using RMGI on the proximal caries surfaces of the primary maxillary incisors were similar.